Pengaruh Penggunaan Media Pop-Up Book Terhadap Motivasi Belajar Siswa pada Pembelajaran Ilmu Pengetahuan Sosial di Madrasah Tsanawiyah Al-Muttaqin Pekanbaru - Nurul Adila; Sakilah; Sukma Erni; Vera Sardila; Ellya Roza; Devi Arisanti (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This research aimed at finding out the effect of Pop-Up Book learning media toward student learning motivation in Social Science learning at Islamic Junior High School of Al-Muttaqin Pekanbaru. This research was instigated with the low of student learning motivation such as students who were less enthusiastic in learning and the lack of learning encouragement. Quantitative approach was used in this research with quasi-experiment method. 255 the seventh-grade students were the population of this research. Purposive sampling was used in this research. The samples used in this research were 68 students. The techniques of collecting data were observation, questionnaire, and documentation. The techniques of analyzing data were quantitative descriptive test, normality test, homogeneity test, hypothesis test, effect size test, and N-gain score test. Based on the research findings and data analyses, Pop-Up Book learning media could affect student learning motivation. It could be proven with the calculation results that the score of fobserved 4.335 was higher than tobe 1.668, and the score of significance 0.000 was lower than 0.05, so He was accepted, and Ho was rejected. The percentage of the effect of Pop-Up Book learning media toward student learning motivation from effect size calculation was 0.53 (0.53%) with moderate effect category.